Gastric duplication presenting as partial gastric outlet obstruction - Giulia Fusi; Francesco Molinaro; Francesco Ferrara; Alessandra Taddei; Franco Roviello; Luigi Marano; Fabiola Rossi; Maurizio Costantini; Alessandro Cappelli; Mario Messina; Rossella Angotti (Elsevier, 2021)
We present a very rare case of gastric duplication treated with complete excision with two surgical procedures. We decided to report our case to share our experience that confirm the difficult of preoperative/intraoperative diagnosis of gastric duplication in a pediatric patient. Finally we reviewed the literature to date.